Prototipe Sistem Monitoring Pelanggaran Zebra Cross di Lampu Merah Berbasis Internet of Things - Jan Revanda Boboy; Emanuel Safirman Bata (JITU : Journal Informatic Technology And Communication, 2023)
Zebra Cross is a facility for pedestrians to cross the highway. In addition, zebra crossing is also a marker for motorists that there are lanes for pedestrians to cross. Because of its function to cross the road, pedestrians need to pay attention to their own safety and smooth traffic when crossing. The problem at the red light is the frequent occurrence of violations. Vehicles that break through when the light is red can cause accidents and even cause fatalities. The accident rate in 2022 is 1,321 incidents. Compared to 2021 there were 1,191 incidents. Meanwhile, the number of traffic violations in 2022/2023 was 25,982 compared to 2021 with 11,316. Therefore, the purpose of this study is to create a monitoring system for violations of the zebra crossing line at red lights. This research was built using the prototyping method and using the ESP32-CAM. From the results of this study a tool was created to detect zebra crossing violations using ultrasonic sensors and ESP32-CAM will automatically send evidence of violations via Telegram.